1999
DOI: 10.1177/00222429990634s116
|View full text |Cite
|
Sign up to set email alerts
|

Marketing, Business Processes, and Shareholder Value: An Organizationally Embedded View of Marketing Activities and the Discipline of Marketing

Abstract: The authors develop a framework for understanding the integration of marketing with business processes and shareholder value. The framework redefines marketing phenomena as embedded in three core business processes that generate value for customers-product development management, supply chain management, and customer relationship management-which in turn creates shareholder value. Such a conceptualization of marketing has the potential to introduce dramatic shifts in the scope, content, and influence of market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
483
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(501 citation statements)
references
References 3 publications
(4 reference statements)
12
483
0
6
Order By: Relevance
“…Companies with this orientation view customers as their most important assets and strike for value creation through managing the relationship with them (Srivastava et al, 1999). It is often suggested that employees are the most critical component of this process (Reinartz et al, 2004;Srivastava et al, 1999). An employee-oriented climate may affect the building of a customer orientation in Chinese subsidiaries in two ways.…”
Section: Employee Orientation and Customer Orientationmentioning
confidence: 99%
“…Companies with this orientation view customers as their most important assets and strike for value creation through managing the relationship with them (Srivastava et al, 1999). It is often suggested that employees are the most critical component of this process (Reinartz et al, 2004;Srivastava et al, 1999). An employee-oriented climate may affect the building of a customer orientation in Chinese subsidiaries in two ways.…”
Section: Employee Orientation and Customer Orientationmentioning
confidence: 99%
“…Thorelli 1986;Williamson 1975). Boundary-spanning activities, rooted in an organization's capabilities (Day 1994), are implemented within customer value-creating processes (Srivastava et al 1999), which are embedded in networks (Achrol and Kotler 1999) to benefit stakeholders (Freeman 1984). As such, marketing activities that are tied to a function or department (Moorman and Rust 1999) are as important as those that are cross-functional, or both, within the boundary-spanning marketing organization (Workman et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Managing customer relationships for value is considered to reflect the essence of the marketing concept and the market orientation literature (Kohli and Jaworski 1990;Morgan and Hunt 1994;Narver and Slater 1990). It is seen as one of the core business processes as well as a strategic imperative (Bohling et al 2006;Srivastava et al 1999). …”
Section: Crm Modelmentioning
confidence: 99%
“…Specifically, we posit that firms with a stronger customer intimacy strategy have a better fit with CRM. Firms that pursue such a strategy consider building long lasting customer relationships as part of creating customer value paramount (Treacy and Wiersema 1993) which fits the ideas behind the CRM practice (Srivastava et al 1999).…”
Section: Controls: -Industry -Firm Size -Customer-centric Management mentioning
confidence: 99%